Integrating business process simulation and information system simulation for performance prediction - Heinrich, Robert; Merkle, Philipp; Henß, Jörg; Paech, Barbara (Software Engineering 2016, 2016)
Business processes (BPs) and information systems (ISs) mutually affect each other in nontrivial ways. Quality issues may arise from missing alignment. Although simulation is a powerful approach to predict the performance of BPs and ISs, current approaches lack their integration in simulation. We propose a holistic performance prediction approach to adequately reflect the mutual impact between BPs and ISs in simulation. Applying the approach and tooling in a real-life case study showed its feasibility and practicability.
Gesehen am 08.06.2020